Real‐World Evidence in Oncology: Opportunities and Limitations. (24th December 2019) - Di Maio, Massimo; Perrone, Francesco; Conte, Pierfranco
Abstract : The analysis of real‐world evidence to answer clinical and policy‐relevant questions in the field of oncology has gained increased interest in recent years. This article highlights the strengths and weaknesses of the use of real‐world evidence in cancer care.